2020
DOI: 10.1186/s12870-020-02384-6
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of polycomb repressive complex 1 and 2 core components in hexaploid bread wheat

Abstract: Background Polycomb repressive complexes 1 and 2 play important roles in epigenetic gene regulation by posttranslationally modifying specific histone residues. Polycomb repressive complex 2 is responsible for the trimethylation of lysine 27 on histone H3; Polycomb repressive complex 1 catalyzes the monoubiquitination of histone H2A at lysine 119. Both complexes have been thoroughly studied in Arabidopsis, but the evolution of polycomb group gene families in monocots, particularly those with com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…We found 64 PcG members in the M. truncatula genome, which was higher than the number found in previous research [ 57 , 58 , 59 , 60 ]. Several researchers identified 10 PcG proteins in M. truncatula [ 57 , 58 ] and 48 PcG proteins in T. aestivum [ 62 ]. Therefore, it is more likely that the number of PcG members in different species was associated with the genome size of the species, ploidy level, analytical method used, and other factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found 64 PcG members in the M. truncatula genome, which was higher than the number found in previous research [ 57 , 58 , 59 , 60 ]. Several researchers identified 10 PcG proteins in M. truncatula [ 57 , 58 ] and 48 PcG proteins in T. aestivum [ 62 ]. Therefore, it is more likely that the number of PcG members in different species was associated with the genome size of the species, ploidy level, analytical method used, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the previously reported MtLHP1 gene was identified based on another genome database (Mt3.5v5 version) [ 60 ], whereas the LHP1 gene of M. truncatula was not identified in this study. Moreover, it was previously reported that the members of FIS2 and MEA have not been identified in O. sativa , T. aestivum , Z. mays , and M. truncatula [ 57 , 58 , 62 , 63 ]. Similarly, we did not identify the member of the FIS2 component in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolutionary studies on the PRC1 subunits (LHP1, Ring1A/1B, BMI1A/1B/1C, EMF1, and VRN1) show that the PRC1 core subunits are conserved in angiosperms [ 34 ], indicating that PRC1 may play similar important regulatory roles in flowering plants. Homologous genes of LHP1 , BMI1A/1B/1C , RING1A/1B , and EMF1 have been discovered in the allohexaploid bread wheat ( Triticum aestivum ) [ 106 ], providing vital tools for studying and manipulating PRC1 in this plant. RING1 , BMI1 and LHP1 are also present in early plant homologs, and have been found in mosses, lycophytes and ferns [ 34 , 107 ].…”
Section: Prc1 and Prc2 In Plants Other Than Arabidopsismentioning
confidence: 99%